Morphology and pathogenicity of Rhizoctonia solani Kühn associated with potato black scurf in Nariño (Colombia) - Betancourth-García, Carlos A.; Castro-Caicedo, Bertha Lucía; Quiroz-Ojeda, Claudia; Sañudo-Sotelo, Benjamin; Florez-Casanova, Carlos; Salazar-González, Claudia (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
The objective of the research was to understand the diversity of Rhizoctonia solani in potato crops in Nariño. Tubers with sclerotia were collected from farms in the municipalities of Pasto, Ipiales, Tuquerres and Ospina. In a laboratory, the strains were grouped in categories, selecting 30 for morphological and pathogenic studies. In an PDA medium, the daily mycelia growth rate (DMGR), pigmentation, texture, growth pattern (GP) and sclerotia characteristics were determined. The hyphae width and nuclei number were also evaluated. Solanum tuberosum L. Group Phureja seedlings were used in the pathogenicity test. Initially, 494 strains were obtained with diverse cultural characteristics, grouped in 15 categories, selecting two of each one for the research. Of the 30 strains, there were significant differences in the DMGR according to the Tukey test (P=0.05), 96.6% of the strains had an average of 16.6 mm day-1. 15 day-old colonies had cream, beige, brown and salmon colors. 95% of the isolates formed plush mycelium with GP concentric simple rings, complex rings, and scattered and stellate forms. Sclerotia formation began at 6 days (average), and, at 15 days, dispersed arrangement predominated, as well as a peripheral, with brown, beige and cream colors. Three isolates did not produce sclerotia. The hyphae had a mean of 9.7 μm, and the nuclei number ranged between 7.2 - 8.2, without statistical differences. Twenty-four isolates caused 100% plant infection. The results suggest differences between the isolates, associated with levels of pathogenicity or anastomosis groups (AG), characteristics that will be studied in future research.